(untitled) (Research, Society and Development, 2022)
Objective: To verify the impact of Wanda Horta’s publications on the consolidation of nursing as a science, through the analysis of scientific publications that used the theoretical framework of Wanda de Aguiar Horta, as well as the Nursing process, practice, relating to the period of consolidation of nursing as a science in Brazil, between the years 60 and 90. Method: A systematic review of the literature was carried out, using a descriptive-analytical-reflexive methodology with historical relevance, with the articles researched from 1960 to 1999, in the databases Literatura Latino-Americana de Ciências da Saúde (LILACS), Scientific Electronic Library Online (SciELO), Medical Literature Analysis and Retrieval System Online (MEDLINE) via PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Fundación Index Cuiden, CAPES Portal and Embase. Results: The analyzed publications describe periods and research drawings more addressed regarding the theme and the use of Wanda Horta’s referential. Final considerations: It highlights the contribution of Horta in the construction of a new knowledge of nursing, based on the development of a theory and a methodology of its own, subsidizing nursing care nowadays in Brazil.